Comparative Study of Acute Lung Injury in COVID-19 and Non-COVID-19 Patients - Zhang, Jianguo; Huang, Xing; Ding, Daoyin; Zhang, Jinhui; Xu, Liusheng; Hu, Zhenkui; Xu, Wenrong; Tao, Zhimin (Frontiers in Medicine, 2021)
Background: Several months into the coronavirus diseases 2019 (COVID-19) pandemic, we analyzed clinical characteristics of acute lung injury (ALI) in COVID-19 patients and reported their similarity and dissimilarity to those of non-COVID-19 patients in the intensive care unit (ICU). Methods: We reported on 90 COVID-19 and 130 non-COVID-19 ALI patients in the ICUs of multiple centers. Demographic data, medical histories, laboratory findings and radiological images were analyzed and compared between the two cohorts and within each cohort between survivors and non-survivors. For ALI survivors clinical characteristics before and after treatment were also compared. Findings: Aberrations in blood parameters, such as leukocytosis, neutrophilia, and thrombocytopenia, were observed in both cohorts. More characteristic abnormalities, including significantly higher red cell distribution width (RDW), C-reactive proteins and lactic dehydrogenase (LDH) but lower troponin (TnT) and procalcitonin were observed in the COVID-19 cohort than in the non-COVID-19 cohort, whereas D-dimer levels showed a similar elevation in both cohorts. The COVID-19 cohort also showed more diversified CT patterns where severe features such as consolidations and crazy paving patterns were more frequently observed. Interpretation: Comparison of ALI characteristics between COVID-19 and non-COVID-19 patients in the ICU setting provided insight into the pathogenesis of ALI induced by different risk factors, suggesting distinct treatment plans.